(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
In this research, erosion wear rate and hardness shore D for polymer biocomposite materials were investigated. The present bio-composites made up of differing weight percentage of pistachio shell powder (0%, 5%, 7%, and 9%) with epoxy resin was prepared by hand layout method. The erosion wear rates for bio composites obtained with under constant factors (10 hours, 60º impingement angles, sand silica particles 850μm, standoff distance 23 cm, flow rate 45 L/min, room temperature, nozzle diameter 4mm and pump diameter 50 mm). Results show that the specimen (epoxy + 9% pistachio shell powder) has the best erosion wear rate resistance and hardness shore D compared with other specimens, also the specimen reinforced by 9% pistachio shell have the lower density and highest water absorption percentage and it is found that the improving percentage for the this specimen in hardness is (11.5%) and in erosion wear rate is (775%). The study reveals that the addition of pistachio shell powder to the epoxy reduces its erosion wear rate and semi ductile behavior.